Unipolar Mania: Recent Updates and Review of the Literature - Mehta, Shubham (Hindawi Publishing Corporation, 2014)
Introduction. Unipolar mania (UM) has received less than the expected attention, when compared to its contemporary mood disorders, unipolar depression (UD) and bipolar disorder (BD). Method. The literature search included PUBMED and PSYCINFO databases. Cross-searches of key references were made to identify other articles of importance. Results. There seems to be a bipolar subgroup with a stable, unipolar recurrent manic course. Although UM does not have significant differences from bipolar mania in terms of sociodemographic variables, there are certain significant differences in clinical features. UM is reported to have more grandiosity, psychotic symptoms, and premorbid hyperthymic temperament, but less rapid cycling, suicidality, seasonality, and comorbid anxiety disorders. It seems to have a better course of illness with better social and professional adjustment. However, its response to lithium prophylaxis is found to be poor as compared to classical BD and valproate could be a better choice in this case. Conclusion. The available literature suggests that UM has certain differences from classical BD. The evidence, however, is insufficient to categorize it as separate diagnostic entity. However, considering UM as a course specifier of BD would be a reasonable step.